THE PRINCIPLE OF POLITENESS: REALIZATION OF COMMUNICATION BETWEEN CHILDREN AND PARENTS - Samsiah, Idhokus (Progressive of Cognitive and Ability, 2025)
This study examines the realization of communication in the family, especially in the form of speech between parents and children and vice versa. This study is relevant in the context of the social life of modern society which has changed due to developments in education and social fields.  This knowledge is very important, by knowing the speech and politeness principles in speaking in the family, we will be able to adjust and behave according to the rules and psychological conditions of the interlocutor as a reflection of how to get along in a pragmatic society. This research is conducted as a case study of family speech in which there are values of politeness and manners as guidelines for human interaction. The presentation of this research is focused on the ethics of speech between a mother and a child related to the principle of politeness in the pragmatic branch of language. This study is conducted with descriptive analysis which can then produce the value of speech ethics in the family related to the principle of politeness and can be used as a reference in life.